Radioactive waste buried beneath Runit Dome on Enewetak Atoll, Marshall Islands. (10th December 2012) - Davisson, M. Lee; Hamilton, Terry F.; Tompson, Andrew F.B.
In the early 1970s after extensive characterisation of fallout the US Pacific Proving Grounds located at Enewetak Atoll began rehabilitation in preparation for the return of indigenous people who were relocated during the Cold War. Cleanup entailed removal and collection of ~545 GBq of contaminated topsoil, vegetation, and debris (concrete and metal) that was subsequently entombed within an unlined crater produced by an 18 kT surface test and capped with a concrete dome. The site is now known as the Runit Dome. Currently, the US Department of Energy conducts comprehensive radiological monitoring of people living on Enewetak Atoll, but characterisation of exposure risks posed by Runit Dome have been limited to catastrophic release scenarios and periodic atoll-wide environmental surveys. Furthermore, evidence indicates open hydraulic communication between waste and intruding ocean water, with migration pathways leading to local groundwater and circulating lagoon waters. Radionuclide migration is likely facilitated by colloids and dissolution/complexation reactions under low-pH anoxic conditions.